Representing Environmental Emergency as Social Emergency: The Great Mississippi Flood of 1927 in Blues Songs from Louisiana and Mississippi - Stéphanie DENÈVE (E-REA)
The Great 1927 Flood ranks as the worst environmental disaster in American history. In the early 20th century, Mississippi floods had been worsening as the levee system progressed, in a period when the development of industrial plantations required the brutal exploitation and control of natural and human resources. While local elites and federal authorities declared war on the Mississippi River and on their black workforce, how did this region’s inhabitants process, interpret, and represent the 1927 flood? Because most of them had no access to publishing, researchers have to turn to their songs, particularly blues songs, to answer these questions.The present article argues that the fate of African Americans in the lower Mississippi basin was inseparable from that of the natural environment and that blues singers represented this environment as an active presence in their lives and saw it as a reservoir of metaphors and signifiers of their condition. Through their songs, they described how they experienced and perceived their interactions with nature, denounced the treatment African-American environmental refugees received, and raised awareness about an issue which is as burning today as it was then – environmental injustice, in a way that still seemed relevant to Hurricane Katrina’s victims almost a century later.